Development of STEAM-based Differentiated Learning Tools on Comparison Material: Efforts to Improve Mathematical Literacy - Pribadi, Maharani Hayuning Pangastuti; Lestari, Nurcholif Diah Sri; Kurniati, Dian; Pambudi, Didik Sugeng; Prihandoko, Antonius Cahya (IndoMath: Indonesia Mathematics Education, 2025)
One of the efforts to improve mathematical literacy is through differentiated and STEAM-based learning. This study aims to develop learning tools (teaching modules, LKPD, manuals and test packages) on comparison materials to improve students' mathematical literacy. This research uses the 4D model with the stages of defining, designing, developing, and disseminating. Data were collected through interviews, literature studies, observations, questionnaires, and tests. The teaching module design applies EDP for 6 JP and LKPD that facilitates process and content differentiated learning. The results of the development stage showed that the learning tools met the criteria: validity with a valid category (at least 3 on a scale of 4); practicality criteria with 87.74% of students active, and 3.68 (maximum scale of 4) learning implemented, as well as 71.67% of positive student responses; effectiveness with 79.2% of students complete learning and N-Gain 0.48 for mathematical literacy improvement. This study recommends that teachers accommodate students' learning needs and activate the classroom atmosphere using the learning tools that have been developed.